2012
DOI: 10.1093/ndt/gfs073
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis and causes of mortality in patients with lupus nephritis

Abstract: Lupus nephritis is associated with a 6-fold increase in mortality compared with the general population. Lupus patients who develop ESRD have a 26-fold excess in the risk of death, which is more than twice the risk associated with malignancy or cardiovascular disease in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
203
2
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(228 citation statements)
references
References 39 publications
11
203
2
6
Order By: Relevance
“…In the latter group, there was no tumor recurrence after a follow-up of 54.0 ± 16.9 months. In this regard, increased long-term risk of malignancy had been reported in LN patients and was associated with excessive mortality [1,32,33]. Data from organ transplant recipients shows that long-term immunosuppressive regimens that include mTOR inhibitors are associated with reduced overall cancer risk when compared to patients not treated with mTOR inhibitors, and the difference is due to a lower incidence of non-melanoma skin cancers and kidney cancers [13,34,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the latter group, there was no tumor recurrence after a follow-up of 54.0 ± 16.9 months. In this regard, increased long-term risk of malignancy had been reported in LN patients and was associated with excessive mortality [1,32,33]. Data from organ transplant recipients shows that long-term immunosuppressive regimens that include mTOR inhibitors are associated with reduced overall cancer risk when compared to patients not treated with mTOR inhibitors, and the difference is due to a lower incidence of non-melanoma skin cancers and kidney cancers [13,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Lupus nephritis (LN) is a serious organ involvement in patients with systemic lupus erythematosus (SLE), and is associated with excessive patient mortality [1,2]. LN can occur in approximately 50% of Caucasian SLE patients, and up to 60-70% in Asian SLE patients [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of patients with ESRD caused by GN incurs an estimated annual cost to Medicare alone of almost $3 billion (1). Mortality in GN increases dramatically after the onset of ESRD (2)(3)(4)(5); however, the relative contributions from generic ESRD-related factors and from the underlying cause of GN to this finding have not formally been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…These drugs for LN are usually selected based on findings of renal biopsy [2]. Yap et al [3] reported that LN was associated with a 6-fold increase in mortality compared with the general population and major causes of death were infection, cardiovascular disease, and malignancy. Kidney biopsy is considered as a gold standard for diagnosing, classifying, and guiding the treatment of LN.…”
Section: Is Urinary Tumor Necrosis Factor-like Weak Inducer Of Apoptomentioning
confidence: 99%